Negative factors Affecting public transport movement in Urban streets - Eshmurotovich , Malikov Ravshanbek; Egamberdiyevich, Odilbek Matyaqubov; Aripovich, Anvar Nazarov (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Urban public transport systems require reliable traffic operations and safe road infrastructure to maintain mobility efficiency and passenger service quality. Specific Background: This study investigates operational constraints affecting bus movement on Alisher Navoi Street in Tashkent, focusing on dedicated bus lanes, geometric lane dimensions, roadside infrastructure, and traffic intensity characteristics. Knowledge Gap: Existing urban traffic lanes and supporting infrastructure do not fully correspond to the geometric and operational requirements necessary for safe and continuous bus movement under high traffic density conditions. Aims: The study aims to identify negative factors affecting public transport movement and to determine scientifically justified measures for improving bus operating speed and traffic safety on urban streets. Results: Traffic observations revealed high vehicle density dominated by passenger cars, with total traffic intensity reaching 4306 vehicles during peak periods. Statistical analysis showed dispersed modal vehicle speeds, with an 85th-percentile speed of 64 km/h and a speed variation range of 55 km/h, indicating inefficient use of street transport capacity. The existing dedicated bus lane width was found to be inadequate for the designated operating speed. After increasing the dedicated bus lane width from 2.2 m to 3.20 m and removing barriers obstructing bus movement, bus operating speed increased from 18 km/h to 22 km/h, while congestion and operational interruptions decreased. Novelty: The study provides a scientifically justified assessment of dedicated lane geometry and roadside operational constraints based on field traffic observations and statistical speed analysis. Implications: The findings support practical road infrastructure modifications for improving public transport reliability, traffic safety, and urban traffic-flow management. Highlights: • Dedicated bus lane expansion increased bus operating speed from 18 km/h to 22 km/h.• Statistical traffic analysis identified dispersed modal speeds and inefficient street capacity utilization.• Removal of roadside barriers reduced operational interruptions within priority transit corridors. Keywords: Dedicated Bus Lane, Public Transport Safety, Traffic Intensity, Urban Traffic Flow, Vehicle Operating Speed